MRI commissioning of 1.5T MR-linac systems – a multi-institutional study. (March 2019) - Tijssen, Rob H.N.; Philippens, Marielle E.P.; Paulson, Eric S.; Glitzner, Markus; Chugh, Brige; Wetscherek, Andreas; Dubec, Michael; Wang, Jihong; van der Heide, Uulke A.
Highlights: A comprehensive commissioning protocol is designed to assess the MRI performance of integrated MR-linac systems. The imaging performance of four recently installed 1.5T MR-linac systems is assessed in a multi-institutional study. A benchmark data set is provided by making the results as well as the corresponding measurement protocols publically available. Abstract: Background: Magnetic Resonance linear accelerator (MR-linac) systems represent a new type of technology that allows for online MR-guidance for high precision radiotherapy (RT). Currently, the first MR-linac installations are being introduced clinically. Since the imaging performance of these integrated MR-linac systems is critical for their application, a thorough commissioning of the MRI performance is essential. However, guidelines on the commissioning of MR-guided RT systems are not yet defined and data on the performance of MR-linacs are not yet available. Materials & methods: Here we describe a comprehensive commissioning protocol, which contains standard MRI performance measurements as well as dedicated hybrid tests that specifically assess the interactions between the Linac and the MRI system. The commissioning results of four MR-linac systems are presented in a multi-center study. Results: Although the four systems showed similar performance in all the standard MRI performance tests, some differences were observed relating to the hybrid character of the systems. Field homogeneity measurements identified differences in the gantry shim configuration, which was later confirmed by the vendor. Conclusion: Our results highlight the importance of dedicated hybrid commissioning tests and the ability to compare the machines between institutes at this very early stage of clinical introduction. Until formal guidelines and tolerances are defined the tests described in this study may be used as a practical guideline. Moreover, the multi-center results provide initial bench mark data for future MR-linac installations.